The level of effectiveness of conducting internships during the new normal towards the career learning and development of 4th year Business Administration students within Manila's University Belt - BAUTISTA, Sharina Joy V., CONTI, Rianne Jayne C., DELOS SANTOS, Kendra Coleen, DUMENSEL, Christine Joy C., FAJECULAY, Danica B., LAGOC, Joven Rey D., MARTINEZ, Irish Ann Corinne S., MILO, George lan V., SALCEDA, Rosita Jayde A., YURTAS, Angeline. 4 0 16; 5 (2022)
Introduction: Work immersion, on-the-job training, and internships; are requirements that students must undergo to complete their tertiary education courses. These are preparatory activities for those people about to enter the workforce, allowing them to experience an office setting to make their professional transition cashier. This has been the primary purpose of an internship program since its inception. Internships are where a student can have practical experience as a professional in an industry or field of their choice (University of Maryland, Baltimore County, n.d.). Through internships, one can expand their knowledge, gain real-world exposure, and determine whether they are in the right career field (College of St. Scholastica, 2022). For interns, it not only develops their capabilities as they learn some of the intricacies of their profession but also allows them to widen their networks and contacts. Additionally, it gives them a glimpse into how a company operates on a managerial and administrative level. It is not only the intern who benefits from this experience. The businesses themselves encourage such programs as it supports the company as well. According to the University of Maryland, Baltimore, internships can become a pipeline for future employees (n.d.). As they take in more workers, someone from the pool could be a valuable asset for them in the future. Interns deal with the low-level work they continue to learn from as they free up time for other employees to do more of their other responsibilities (Indeed, 2022). These new faces could also reinvigorate the workforce and offer ideas to aid business operations. As these activities continue to get promoted, they will be able to garner the public's approval and help improve their image. However, these systems that we are accustomed to and the rest of the world suddenly came to a screeching halt as the COVID-19 outbreak was declared a pandemic on March 11, 2020 (World Health Organization, 2020). With the changes brought about by the pandemic, society had to adapt their daily lives to the situation surrounding them. Businesses started to encourage more remote working, as did educational institutions. Those same workers and students faced the most challenges, as reported that at least 463 million children did not have access to remote learning in 2020 (United Nations International Children's Emergency Fund, 2022). The pandemic also highlighted the vulnerabilities in higher education, including concerns of inequality in treatment based on background and inaccessibility of the basic requirements of digital education and information (United Nations Educational, Scientific, and Cultural Organization, 2022). Due to the pandemic, the lives of the students were heavily affected. Their struggles in their personal lives also limited their involvement with education, including internship programs. Because of these supposed challenges, 22% of college students who were part of an internship program indicated a low-quality evaluation for online internships, with only half being in-person positions (Gray, K.. 2021). The difficulties include but are not limited to, equipment and technological issues, internet access issues, communication issues, and more. It is also worth noting that those from upper-income families were more likely to be participating in online Internships. However, the onset of this online experience also allowed the interns to develop technical skills due to the remote nature of their work (Teng et al., 2021). In this study, the researchers aim to gauge how the internship system that once allowed students to experience life as a worker fared during the New Normal, specifically towards Business Administration students from Manila's University Belt.
Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2022.
Keywords: 2 -- 0; 6; 20; 20; 2